COVID19 Pandemic and Mental Health - Cruz, Camila Neres da (Universidade Estadual Paulista (Unesp), 2020)
In this episode of the Foreign Language Learner Podcast, a student in the second year of Language Teaching at Unesp - São José do Rio Preto talks about living in the Covid19 pandemic.
Nível de proficiência de produção oral autoavaliado pelo aluno: B1
Keywords: COVID19 Pandemic; English language Pronunciation by foreigners; Mental Health; COVID-19; Pandemias; Saúde mental; Língua inglesa Pronúncia estrangeira